Acute kidney injury: a COVID-19 update. (2nd January 2021) - Main, Claire
Abstract : Claire Main, Interim Manager of Critical Care and Major Trauma at Cardiff and Vale University Health Board and ANN UK executive board member, gives an update on acute kidney injury and the impact of the COVID-19 pandemic